1953
DOI: 10.1084/jem.98.6.565
|View full text |Cite
|
Sign up to set email alerts
|

Regression of Transplanted Lymphomas Induced in Vivo by Means of Normal Guinea Pig Serum

Abstract: In the experiments here described transplanted lymphomas of two kinds regularly regressed following repeated injections of normal guinea pig serum intraperitoneally into mice carrying them, the animals meanwhile remaining lively and devoid of signs of illness or wasting. The lymphomas of untreated control mice, by contrast, usually grew progressively and killed their hosts within 20 to 30 days, and the same was true of the growth of other mice given repeated injections of horse serum or rabbit serum. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
70
0
5

Year Published

1961
1961
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 354 publications
(75 citation statements)
references
References 0 publications
0
70
0
5
Order By: Relevance
“…The potential use of L--asparaginase to treat cancer was discovered when it was noted that guinea pig serum, but not that of other animals, had an inhibitory effect on the proliferation of lymphoma cells in mice 156 . Guinea pigs are relatively unique among mammals in having serum aspariginase activity 157 , which was found to be responsible for the anti--lymphoma effect in mice 55,158 .…”
Section: Box 2 Development Of L--asparaginase To Treat Allmentioning
confidence: 99%
“…The potential use of L--asparaginase to treat cancer was discovered when it was noted that guinea pig serum, but not that of other animals, had an inhibitory effect on the proliferation of lymphoma cells in mice 156 . Guinea pigs are relatively unique among mammals in having serum aspariginase activity 157 , which was found to be responsible for the anti--lymphoma effect in mice 55,158 .…”
Section: Box 2 Development Of L--asparaginase To Treat Allmentioning
confidence: 99%
“…In a seminal publication from 1953, John G. Kidd reported the unexpected observation that guinea pig serum has the ability to inhibit the growth of subcutaneous lymphomas transplanted into mice (1). It took a further 10 years before the serum ingredient responsible for this effect was revealed to be an enzyme with L-asparaginase activity (2).…”
mentioning
confidence: 99%
“…Vijayalakshmi et al, [14] reported the L-asparaginase producing species of Arthrobacter from mango orchards. Salini et al [75] isolated glutaminase free Lasparaginase producing endophytes from three mangrove species namely Rhizophora mucronata, Excoecaria agallocha, and Sonneratia caseolaris. The strains obtained were usually isolated by nutrient agar medium.…”
Section: Isolation and Screeningmentioning
confidence: 99%